Analyzing Indicators Affecting Commercial Property Value in Metro Station Accessible Area Using Walking Time Consumption: Case of Xi’an, China - Zhen Cao; Xingliang Liu; Bin Lei; Changjiang Liu; Lizhu Jing (Complexity)
In studies investigating the property value enhancements along metro lines, study ranges in most cases are measured in Euclidean distance. However, city roads are not always straight, and Euclidean distance sometimes does not equal to actual distance the passenger travels from the public transport station to their home or a commercial spot. To solve this problem, this study analyzed the indicators affecting commercial property value in metro station accessible area in Xi’an, using walking time consumption in measuring the study range. Following a conceptual framework, considering empirical evidences in related studies, information in city structure, and metro distribution, the initial indicator set is built. Using hedonic price model (HPM), spatial autoregressive model (SAR), and error term (SEM), significant indicators affecting commercial property value are investigated. In this study, 14 significant indicators are determined and quantified. Threshold distance equals to 900 m is found to be appropriate in addressing the autocorrelation problem with the weighted decision matrix tool. Compared to HPM and SEM, SAR is found to perform the best in evaluating the significant indicators with the largest R2 (0.415) and the lowest Akaike Info Criterion (AIC) (−395.214). Besides, it is discovered that the value of the commercial property lies in the study range of 20 min walking time and is obviously influenced by the metro station. The results discovered in this study could provide some empirical evidences to commercial property planning in Xi’an.